LADDER DRILL DAPAT MENINGKATKAN KECEPATAN LARI PEMAIN SEPAK BOLA USIA 15 – 17 - Sukarman, Sukarman (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The basic problem of the authors in conducting this research is that the playing tactics of the players are still not optimal or any strategy that relies on the speed of early age players is still feeling overwhelmed, so that an initiative appears to train the player’s speed. The purpose of this study was to determine the effect of ladder drill on running speed in soccer athletes aged 15-17 in 2020. The research method used in this study was the experimental method. The sampling technique in this study was to use all SSB leaders aged 15-17 years. The instrument used in this study was a speed test with a distance of 30 meters. The data analysis used to process the test result data in the field was using the t-test formula. And the results of this study are that there is an increase due to ladder drill training on running speed in soccer athletes aged 15-17